Effectiveness Of Telehealth Use in Improving the Psychological Health and Quality of Life On Elderly at Home: Efektivitas Penggunaan Telehealth Dalam Meningkatkan Kesehatan Psikologis dan Kualitas Hidup Pada Lansia di Rumah - Efendi, Jamilatur Rasyidah; Sukihananto, Sukihananto (Essential English Grammar, 2024)
The aging process is a process that occurs naturally. When humans reach old age, anatomical, physiological, and biochemical changes occur in body tissues, thus affecting the body's functions and abilities. Various kinds of health programs for the elderly are implemented to improve the health of the elderly, one of which uses telehealth or telemedicine. This literature study aims to describe the use of telehealth in improving the health of the elderly. The method used was a literature review with the keywords elderly, telehealth, telemedicine, eHealth, and mobile health from several ClinicalKey Nursing, EBSCO, Proquest & Scopus databases and published from 2018 to 2023. Study results and review of 10 journal articles concluded that teleheatlh can be considered an important tool to improve aspects of the psychological health and quality of life of the elderly, potentially reducing access to health services, hospitalizations, and costs. Thus, nurses must improve their abilities in technology and nursing information systems. Further studies are needed regarding the use of telehealth in improving the quality of life of the elderly which can be applied in Indonesia.